Cycle time analysis of automation system using PLC and HMI based Scara Robot - Vikry Alvi Putra; Risfendra (Journal of Industrial Automation and Electrical Engineering, 2025)
This article discusses about the design of palletizing machine automation system using SCARA robot based on PLC and HMI. The purpose of this design is to be able to perform programming on the SCARA Robot using a Programmable Logic Controller (PLC), design an interface design for the control system and monitor the system response using a Human Machine Interface (HMI). And test the functional performance of the SCARA T3 robot. The design is supported by Siemens S7-1200 PLC device and Siemens KTP-700 Basic PN HMI. A series of programming processes and making system interfaces are carried out using Epson RC + 7.0 and TIA Portal software. The results of the test can be concluded the design of the palletizing machine automation system can run well at 80% high speed with a 100% success percentage and 0% error percentage.